Accuracy and reliability of Sage Analytics tracking system based on UWB technology for indoor team sports - Hulka, K.; Strniste, M.; Prycl, D. (International Journal of Performance Analysis in Sport, 2020)
Reliability and accuracy of Sage Analytics system for team games is currently unknown. Therefore, the aim of this study is to assess validity and reliability of SAGE Analytics during prescribed movements and specific basketball movements. Eighteen male basketball players completed straight line movements (28 m), zig zag movements (20 m) by walking, jogging and sprinting, and 4 on 4 small-sided game measured by Sage and VideoManualMotionTracker 1.0. Results: System seems to underestimate distance in protocols with changes of directions (2.09-3.49%) and slightly overestimate straight locomotion (1.91-2.38%). At the same time change of direction measurement protocol showed lower error than straight measurement protocol. System showed high reliability (r = 0.985, SEM = 1.42 m). Sage Analytics system was confirmed as a sufficient accurate and reliable tool to determine total distance.